A Holocene paleotemperature record based on radiolaria from the northern Okinawa Trough (East China Sea) - Chang, Fengming; Li, Tiegang; Zhuang, Lihua; Yan, Jun (Quaternary International, 2008)
Using a radiolarian-based transfer function, mean annual sea surface temperature (SST) and seasonal temperature range are reconstructed through the last 10,500yrs in the northern Okinawa Trough. Down-core SST estimates reveal that throughout the Holocene the changes of mean annual SST display a three-step trend: (i) an early Holocene continuous warming between 10,500 and 8500yr BP which ends up with a abrupt cooling at about 8200yr BP; (ii) a relatively stable middle Holocene with high SST that lasted until 3200yr BP; and (iii) a late-Holocene distinct SST decline between 3200 and 500yr BP. This pattern is in agreement with the ice core and terrestrial paleoclimatic records in the Chinese continent and other regions of the world. Five cooling events with abrupt mean annual SST drops, which occur at similar to 300-600, 1400, 3100, 4600-5100 and 8200yr BP, are recognized during the last 10,500yrs. Comparison of our results with records of GISP2 ice core and marine sediment in North Atlantic region suggests these cooling events are strongly coupled, which implies a possible significant climatic correlation between high- and low-latitude areas. (C) 2007 Elsevier Ltd and INQUA. All rights reserved.
id: 1926; PT: J; UT: WOS:000257255700009